Development Of Sample Preparation Techniques For The High Performance Liquid Chromatographic Determination Of Biogenic Amines In Foods - Saaid, Mardiana (2010)
Biogenic amines (BA) have been extensively studied in recent years due to their potential toxicity and possible use as chemical markers for assessing food quality and in cancer research. This thesis is focused on the development of sample preparation techniques for the high performance liquid chromatographic-ultraviolet determination of BA in food. The BA tryptamine (TRP), putrescine (PUT), histamine (HIS), tyramine (TYR) and spermidine (SPD) were extracted using hydrochloric acid and trichloroacetic acid and determined in sixty-two food items commonly consumed in Malaysia. This includes the local appetizers budu and cincalok, canned fish, salt-cured fish, meat products, fruit juice, canned vegetables/fruits and soy bean products. After the extraction, the samples were derivatized with dansyl chloride. Mean levels of TRP, PUT, HIS, TYR and SPD in eight budu samples were 82.7, 38.1, 187.7, 174.7 and 5.1 mg kg–1, respectively. The main BA found in cincalok were PUT, HIS and TYR where the mean values were 330.7, 126.1 and 448.8 mg kg–1, respectively. With the exception of pekasam and belacan, significantly lower levels of BA were found in salt-cured fish samples. Non detectable or low levels of BA were found in meat products, fruit juice and canned vegetables/fruit samples.